Efficient Synthesis of Novel Pyridine-Based Derivatives via Suzuki Cross-Coupling Reaction of Commercially Available 5-Bromo-2-methylpyridin-3-amine: Quantum Mechanical Investigations and Biological Activities - Gulraiz, Ahmad; Rasool, Nasir; Ikram, Hafiz Mansoor; Khan, Samreen Gul; Mahmood, Tariq; Ayub, Khurshid; Zubair, Muhammad; Al-Zahrani, Eman; Rana, Usman Ali; Akhtar, Muhammad Nadeem; Noorjahan Banu, Alitheen (MDPI - Open Access Publishing, 2017)
The present study describes palladium-catalyzed one pot Suzuki cross-coupling reaction to synthesize a series of novel pyridine derivatives 2a–2i, 4a–4i. In brief, Suzuki cross-coupling reaction of 5-bromo-2-methylpyridin-3-amine (1) directly or via N-[5-bromo-2-methylpyridine-3-yl]acetamide (3) with several arylboronic acids produced these novel pyridine derivatives in moderate to good yield. Density functional theory (DFT) studies were carried out for the pyridine derivatives 2a–2i and 4a–4i by using B3LYP/6-31G(d,p) basis with the help of GAUSSIAN 09 suite programme. The frontier molecular orbitals analysis, reactivity indices, molecular electrostatic potential and dipole measurements with the help of DFT methods, described the possible reaction pathways and potential candidates as chiral dopants for liquid crystals. The anti-thrombolytic, biofilm inhibition and haemolytic activities of pyridine derivatives were also investigated. In particular, the compound 4b exhibited the highest percentage lysis value (41.32%) against clot formation in human blood among all newly synthesized compounds. In addition, the compound 4f was found to be the most potent against Escherichia coli with an inhibition value of 91.95%. The rest of the pyridine derivatives displayed moderate biological activities.